INTEGRASI METODE FUZZY ANALYTICAL HIERARCHYPROCESS (F-AHP) DAN TECHNIQUE FOR ORDERPREFERENCE BY SIMILARITY TO IDEAL SOLUTION(TOPSIS) UNTUK PEMILIHAN SUPPLIER BIJI PLASTIKPOLYPROPYLENE PADA PT.XYZ - Diantya Pitaloka Musetyoputri (2021)
Selection of suppliers is important because suppliers play a role in ensuring the availability of supplies of raw materials and products needed by the company in the production process. PT. XYZ is a company that produces raffia rope. PT. XYZ has problems, namely, the quality of the parent material is not maintained, the old supplier does not allow the return of the parent material, the quantity of the parent material is not stable, has problems with delays in delivery of goods. Therefore, PT. XYZ tries to find three other suppliers, including PT. A, PT. B, and PT. C as an alternative supplier of choice. This causes PT. XYZ to determine a permanent supplier based on criteria and sub-criteria that are in accordance with the company's conditions and objective calculations. Fuzzy AHP and TOPSIS are examples of decision-making methods that can be used as a basis for supplier selection. Fuzzy AHP aims to obtain the weight of each criterion, then TOPSIS aims to rank the alternatives. The research data was obtained from the results of interviews and filling out questionnaires by the Factory Director. There are 4 criteria used in this study, namely Quality (Q), Price (C), Production (P), Delivery (D). TOPSIS method, PT. A with a preference value of 0.53179, PT. B with a preference value of 0.62244, PT. C with a preference value of 0.22597. The results showed that PT. B is a supplier of Polypropylene plastic seeds for PT. XYZ because it has the highest preference value.